DOES GREEN INNOVATION MEDIATE GREEN SUPPLY CHAIN MANAGEMENT AND FIRM VALUE? - Lutfiya, Afifah Astri; Widiastuty, Erna (Jurnal Aplikasi Akuntansi, 2026)
This study aims to provide empirical evidence on the mediating role of green innovation in the effect of green supply chain management on firm value. The research sample consists of PROPER companies listed on the Indonesia Stock Exchange for the 2019–2024 period. Sampling was conducted using a purposive sampling technique, yielding a sample in 124 companies. The data sources come from company annual reports, sustainability reports, and Datastream. The dependent variable is firm value, measured by Tobin’s Q, while the independent variable is green supply chain management, measured using a checklist. The mediating variable is green innovation, measured using a checklist. Empirical evidence shows that green innovation mediates the effect of green supply chain management on firm value. The findings indicate that green supply chain management is not merely a regulatory compliance mechanism but a strategic approach to enhancing firm value.